Uji Pertumbuhan dan Produksi Ubi Jalar (Ipomoea batatas L.) Terhadap Model Tanam Dan Interval Penyiangan Gulma - Rohaeni, Nani; Marhani, Marhani (Jurnal Pertanian Terpadu, 2018)
Nani Rohaeni dan Marhani. Agrotechnology Studies Program Sekolah Tinggi Pertanian Kutai Timur, 2018. Plant grownt test-S and production of sweet potato (Ipomoea batatas L.) on the planting model and weed mowing interval. This research aims to determine the effect of the best planting mode model and weed mowing interval on the growth and yield of sweet potato crops (Ipomoea batatas L.). This research was conducted for 4 months, from April to July 2017, starting from the preparation of the place to the last data collection / harvest. This research is located on ring road road, South Sangatta, East Kutai. The method used in this research is factorial randomized block design (RAK) consisting of 2 factors and repeated 3 times so that there will be 36 plot of research. The first factor is the way of planting treatment which consists of, C1 = sloping, C2 = upright, C3 = flat. Second factor is the weeding (p) ,consist which from PO = without weeding, P1 = weeding weeds every 1 week, P2 = weeding weeds every 2 weeks, P3 = weeding weeds every 3 weeks. Data analysis using tables of analysis of variance with continued test of Smallest Differentiated (BNT) 5%. Result of research indicate that treatment of planting method is significantly different to plant length aged 4 MST, 8 MST, 10 MST. Amount of branches at age 8 MST and 10 MST, weight of fresh bulbs and production. The treatment of sloping planting with the weeding interval of 2 weeks gave the best result